Priorities and Challenges Accessing Health Care Among Female Migrants - Samantha R Lattof; Ernestina Coast; Tiziana Leone (SAGE Publishing, 2018)
Women's ability to access health care requires access to and control of resources as well as the ability to make personal health decisions. Female migrants may experience additional challenges in accessing health care due to marginalization and vulnerability resulting from both their gender and their migrant status. Rural-to-urban migrant women working in the informal sector, such as Ghana's head porters ( kayayei ), experience exclusion from the health system, risk of being uninsured, and poor health outcomes. Kayayei's survival needs (eg, food, water) and a need to provide for their families can mean that migrant kayayei avoid health care expenses for illnesses or injuries. To ensure equal access to health care for migrant and non-migrant populations, health insurance is crucial. Yet, improving access to health care and service uptake requires more than health insurance. Incorporating culturally appropriate care into the provision of health services, or even developing specific migrant-friendly health services, could improve health service uptake and health awareness among migrants. Public health systems should also take account of migrants' financial situations and priorities in the design and delivery of health services.